Micro-, Macro-, and Meta-Cosmos of Keduk Beji Ritual: Harmonising the “Un-/Living” Creatures - Annysa Endriastuti; Eko Kusumo (Kawalu: Journal of Local Culture, 2017)
The process of how Javanese life worksin harmony with these three core relationships namely: human relations (microcosm), relationship with nature (macrocosm), and relationship with God (metacosm)is the main focus of this study. The people of Tawun District, Ngasreman, Ngawi, East Java,as the object of this study are likely to offer so much understanding, and indeed provide still, today, a harmonious concept of livingmanifested in the ritual ceremony of Keduk Beji (English: Beji scoop). This study then examines howthe construction of microcosm, macrocosm, and metacosm among Tawunpeople’sritual tradition of Keduk Bejiis put to work. The constructions are built upon the need for continuity and harmony in life. For the conclusion, this article’s preliminary result of the three relationships is centered on the relationship of metacosm as the last objectives of mankind before dealing withthe death. To fully support this field research article, a qualitative method is used to fully comprehend the analysis.